2021
DOI: 10.1021/acs.macromol.1c00613
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Optical Anisotropy in Chitosan Thin Films: Role of Swelling

Abstract: Thin films of chitosan, a biopolymer, have attracted attention as plausible candidates for several niche applications. Such uses would be better served by a deeper understanding of the physical characteristics of the films and their relationship to polymer confinement. Therefore, we have used spectroscopic ellipsometry to investigate the optical properties of chitosan thin films prepared by spin coating. Thin films of chitosan exhibited uniaxial anisotropy with a higher in-plane refractive index. This suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 64 publications
3
6
0
Order By: Relevance
“…We found that the swelling of the thin films could be expressed using an ''effective swelling ratio'', c(t), for all of the investigated films irrespective of their initial (dry) thickness, provided there existed a tightly bound polymer layer of thickness E15 nm at the polymer/substrate interface that could not swell upon exposure to H 2 O vapour. The results for PVA were comparable to our earlier results 18 for a different hydrophilic polymer, chitosan, where the bound layer thickness was found to be E19 nm. XRR measurements were performed on two of the PVA thin films whose initial (dry) thicknesses were 18 nm and 58 nm.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that the swelling of the thin films could be expressed using an ''effective swelling ratio'', c(t), for all of the investigated films irrespective of their initial (dry) thickness, provided there existed a tightly bound polymer layer of thickness E15 nm at the polymer/substrate interface that could not swell upon exposure to H 2 O vapour. The results for PVA were comparable to our earlier results 18 for a different hydrophilic polymer, chitosan, where the bound layer thickness was found to be E19 nm. XRR measurements were performed on two of the PVA thin films whose initial (dry) thicknesses were 18 nm and 58 nm.…”
Section: Discussionsupporting
confidence: 89%
“…For all of our samples, adequate fits, as indicated by the mean square error (MSE) values ≤10 (the larger values were obtained for the thicker films) could be obtained. Similarly to earlier investigations, 18,39,41,42,44 we found that adequate fits, as indicated by a negligible increase in the MSE values, could be obtained even by setting C = 0 in eqn (2). Therefore, to reduce the number of fit parameters, C = 0 was used for all of the fits performed in this work.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations